2021
DOI: 10.17645/mac.v9i1.3433
|View full text |Cite
|
Sign up to set email alerts
|

Deepfakes on Twitter: Which Actors Control Their Spread?

Abstract: The term deepfake was first used in a Reddit post in 2017 to refer to videos manipulated using artificial intelligence techniques and since then it is becoming easier to create such fake videos. A recent investigation by the cybersecurity company Deeptrace in September 2019 indicated that the number of what is known as fake videos had doubled in the last nine months and that most were pornographic videos used as revenge to harm many women. The report also highlighted the potential of this technology to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Considering the economics of emotions (Bakir and McStay, 2018), FNI leverages emotions to generate attention and produce a surge of clickbait to attract diverse audiences (Munger, 2020). As Internet users are more likely to trust images and audio, deepfakes have quickly become a popular form of fake news (Ahmed, 2021b;Dasilva et al, 2021;Vaccari and Chadwick, 2020;Wahl-Jorgensen and Carlson, 2021). Regarding other links, root tweets about fake news are mostly generated by ordinary accounts, but they often include a link to non-credible news websites .…”
Section: Input Of Fnimentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the economics of emotions (Bakir and McStay, 2018), FNI leverages emotions to generate attention and produce a surge of clickbait to attract diverse audiences (Munger, 2020). As Internet users are more likely to trust images and audio, deepfakes have quickly become a popular form of fake news (Ahmed, 2021b;Dasilva et al, 2021;Vaccari and Chadwick, 2020;Wahl-Jorgensen and Carlson, 2021). Regarding other links, root tweets about fake news are mostly generated by ordinary accounts, but they often include a link to non-credible news websites .…”
Section: Input Of Fnimentioning
confidence: 99%
“…, 2016). Deepfakes are an emerging form of disinformation involving doctored multimedia content (Ahmed, 2021c; Dasilva et al. , 2021; Vaccari and Chadwick, 2020; Wahl-Jorgensen and Carlson, 2021).…”
Section: Research Design and General Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Westerlund (2019) argues that celebrities are easy targets for fabricated content since they have an abundance of free video, image, and audio content circulating over the internet and that content availability facilitates deepfakes creation. Dasilva et al (2021) analyzed the debate around deepfakes on a Twitter network. They have shown that journalists and media are bridging information nodes and that celebrities figures are among the most referenced and virialized users in the networks.…”
Section: Final Considerations and Future Agendamentioning
confidence: 99%
“…Twitter lucha con ocho millones de cuentas a la semana que intentan difundir contenido manipulado. Deepfakes publicados y compartidos en Twitter acumulan millones de visualizaciones (Pérez et al, 2021).…”
Section: Métodos Para Combatir Las Falsificaciones Profundasunclassified